An Analysis of Affixation Processes of Derivation and Inflection in Article with the Title “The Government of the Republic of Indonesia” - Made Prima Devi Hutaminingrum (Linguistics Initiative, 2022)
This study aims to analyze the derivational and inflection affixation processes in the article entitled "The Government of The Republic of Indonesia". The author also describes the affixation that occurs in sentences or words contained in the article. To make it easier to see derivational and inflectional affixations, the authors use a table to determine each affixation process found. This study explores English words that experience derivational and inflection affixation processes. The source of the data studied is a written text, so this study will use the documentation method. The writer found that there were 24 affixes, namely derivational and inflectional. Of the 24 affixes found in the articles studied, 17 affixes were given derivational affixes and 7 affixes that were affixed with inflections. From the results of the analysis that has been carried out by the researcher, it can be concluded that in the article entitled "The Government of The Republic of Indonesia", there are words that are given affixation process affixes such as derivational and inflection.